1984
DOI: 10.1364/ol.9.000137
|View full text |Cite
|
Sign up to set email alerts
|

Integrated optical switches and gas sensors

Abstract: We have demonstrated new switching and gas-sensing effects in integrated optics using input and output grating couplers and Bragg reflector gratings with 1200 lines/mm on planar SiO(2)-TiO(2) waveguides. Switching is actuated by adsorption or desorption of water or other adsorbates on the waveguide surface through a change in the effective index of the guided modes under the grating. We derived theoretically the ultimate sensitivity limits of the grating devices employed either as switches or as gas sensors. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
4

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(39 citation statements)
references
References 2 publications
0
35
0
4
Order By: Relevance
“…However, Tiefenthaler and Lukosz demonstrated that switching and sensing devices could be achieved by using adsorption or desorption of a monolayer of water molecules on the surface of a short period relief grating coupler fabricated on planar waveguides. 7 More recently Rees and co-workers 8 have reported resonant shifts in LPGs with films of subwavelength thickness, using Langmuir-Blodgett ͑LB͒ films. The observed optical response was relatively small with maximal shifts of 10 nm in wavelength with 400 nm of deposited film.…”
mentioning
confidence: 99%
“…However, Tiefenthaler and Lukosz demonstrated that switching and sensing devices could be achieved by using adsorption or desorption of a monolayer of water molecules on the surface of a short period relief grating coupler fabricated on planar waveguides. 7 More recently Rees and co-workers 8 have reported resonant shifts in LPGs with films of subwavelength thickness, using Langmuir-Blodgett ͑LB͒ films. The observed optical response was relatively small with maximal shifts of 10 nm in wavelength with 400 nm of deposited film.…”
mentioning
confidence: 99%
“…Biochemical sensors have been receiving more interest due to their features over other sensors such as high sensitivity, low cost, reduced size, and the possibility of operation in aggressive environments. Tie− fenthaler and Lukosz introduced for the first time a planar optical waveguide for gas and humidity sensing by measur− ing the change in the refractive index of the material con− tained in the waveguide cover [16]. Since then tremendous advances in slab waveguide sensors have taken place for humidity, gas, chemical, and biochemical sensing [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The said effects bring about the change of effective refractive in− dexes of modes propagating in the structure. The changes of effective refractive indexes can be measured by the applica− tion of the interferometers of Mach−Zehnder [4,5], Young [6,7] and with a polarimeter [1,[8][9][10] or grating couplers [3,[11][12][13][14][15][16][17][18]. In chemical and biochemical measurements, surface plasmon resonance sensors are also applied [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore they can be applied to determine the absolute value of the refractive index of the uniform cover or to determine the thickness and the refractive index of the sensitive film. Grating couplers as sensor ele− ments were for the first time applied by the research team led by Lukosz [11,12]. The application of grating couplers for sensor application has been also intensively investigated by Kuntz et al [13][14][15], and by Vörös, Szendrö, and Horváth [16,17].…”
Section: Introductionmentioning
confidence: 99%